Effect of vitamin B deprivation during pregnancy and lactation on homocysteine metabolism and related metabolites in brain and plasma of mice offspring. - Vanessa Cavalcante da Silva; Leandro Fernandes; Eduardo Jun Haseyama; Ana Luiza Dias Abdo Agamme; Elvira Maria Guerra Shinohara; Maria Tereza Cartaxo Muniz; Vânia D'Almeida (PLoS ONE)
Epidemiological and experimental studies indicate that the altered fetal and neonatal environment influences physiological functions and may increase the risk of developing chronic diseases in adulthood. Because homocysteine (Hcy) metabolic imbalance is considered a risk factor for neurodegenerative diseases, we investigated whether maternal Vitamin B deficiency during early development alters the offspring's methionine-homocysteine metabolism in their brain. To this end, the dams were submitted to experimental diet one month before and during pregnancy or pregnancy/lactation. After birth, the offspring were organized into the following groups: control (CT), deficient diet during pregnancy and lactation (DPL) and deficient diet during pregnancy (DP). The mice were euthanized at various stages of development. Hcy, cysteine, glutathione (GSH), S-adenosylmethionine (SAM), S-adenosylhomocysteine (SAH), folate and cobalamin concentrations were measured in the plasma and/or brain. At postnatal day (PND) 0, total brain of female and male offspring exhibited decreased SAM/SAH ratios. Moreover, at PND 28, we observed decreased GSH/GSSG ratios in both females and males in the DPL group. Exposure to a Vitamin B-deficient diet during the ontogenic plasticity period had a negative impact on plasma folate and brain cortex SAM concentrations in aged DPL males. We also observed decreased plasma GSH concentrations in both DP and DPL males (PND 210). Additionally, this manipulation seemed to affect the female and male offspring differently. The decreased plasma GSH concentration may reflect redox changes in tissues and the decreased brain cortex SAM may be involved in changes of gene expression, which could contribute to neurodegenerative diseases over the long term.